Career Planning of Scientific-Pedagogical Personnel in Higher Education Institutions - Litynska, Valentyna; Kondratska, Ludmyla; Romanovska, Liudmila; Kravchyna, Tetiana; Chagovets, Alla; Kalaur, Svitlana (European Journal of Sustainable Development, 2023)
The article systematizes approaches to the interpretation of the concepts "career" and "career planning" of scientific-pedagogical personnel in higher education institution. The structural-logical scheme for the step-by-step career planning of higher education institutions’ scientific-pedagogical personnel is developed in the article. It is proposed to use 6 consecutive stages for planning the career of scientific-pedagogical personnel: making a management decision on the feasibility and necessity of organizing the career planning of scientific-pedagogical personnel in higher education institution, developing a plan-schedule for planning the career of scientific-pedagogical personnel of higher education institution, formation of initial database of individual data of higher education institutions’ scientific-pedagogical staff, assessment of professional and personal qualities of scientific-pedagogical staff of higher education institution, development of individual career planning maps of scientific-pedagogical staff of higher education institution, formation of favorable social and psychological conditions of successful career advancement of scientific-pedagogical staff of higher education institution. In addition, at each stage, it is absolutely necessary to monitor the implementation of the career plan of scientific-pedagogical personnel. With the help of correlation analysis, the conformity indicators of scientific-pedagogical personnel (which must be used at the stage of evaluating their professional and personal qualities) are determined. Keywords: Career; Planning; Education, Conformity Indicators; Correlational Analysis